ANALISIS SENTIMEN TERHADAP PEMUTUSAN HUBUNGAN KERJA DI INDONESIA : KOMPARASI INDOBERT DENGAN SVM, RANDOM FOREST, DAN DECISION TREE DENGAN OPTIMASI TF - IDF - Nida Nur Aini Aryanti; Ozzi Suria (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
Employment termination (PHK) has become a crucial issue widely discussed on social media platforms like Twitter due to its social and economic impacts. This study aims to analyze public sentiment toward PHK in Indonesia using four classification methods: IndoBERT, Support Vector Machine (SVM), Random Forest, and Decision Tree. The data were collected via Twitter crawling using the keyword "PHK” in Bahasa Indonesia during the period from January to May 2025, resulting in 36,507 tweets. The data underwent preprocessing steps including case folding, cleaning, tokenization, normalization, stopword removal, and stemming. Text features were transformed into numerical form using the TF-IDF for classical models and IndoBERT tokenizer for the transformer-based model. Sentiments were classified into positive, negative, and neutral categories. Model performance was evaluated using a Confusion Matrix with an 80% training and 20% testing data split. Results show that the IndoBERT achieved the highest accuracy at 89,6%, SVM algorithm achieved accuary 88%, precision 90%, recall 95%, F1-score 92%, followed by Random Forest at 78.04%, and Decision Tree at 70.40%. Negative sentiment dominated with 21,790 tweets, reflecting significant public concern over PHK policies. This study concludes that SVM with the TF-IDF approach is the most effective model for real-time public sentiment classification. The limitation of this research lies in the data source, which is exclusively from Twitter and limited to a specific time frame, thus not representing the overall public opinin comprehensively.